Comparing Cognitive Profiles of Licensed Drivers with Mild Alzheimer's Disease and Mild Dementia with Lewy Bodies - Yamin, Stephanie; Stinchcombe, Arne; Gagnon, Sylvain (Université d'Ottawa | University of Ottawa, 2016)
Purpose. Alzheimer's disease (AD) and dementia with Lewy Bodies (DLB) constitute two of the most common forms of dementia in North America. Driving is a primary means of mobility among older adults and the risk of dementia increases with advanced age. The purpose of this paper is to describe the cognitive profile of licensed drivers with mild AD and mild DLB. Method. Licensed drivers with mild AD, mild DLB, and healthy controls completed neuropsychological tests measuring general cognition, attention, visuospatial/perception, language, and cognitive fluctuations. Results. The results showed differences between healthy controls and demented participants on almost all neuropsychological measures. Participants with early DLB were found to perform significantly worse on some measures of attention and visuospatial functioning in comparison with early AD. Discussion. Future research should examine the relationship between neuropsychological measures and driving outcomes among individuals with mild AD and mild DLB.